Սուրբ Ներսէս Շնորհալու Թուղթ ընդհանրական երկը - Մալոյեան, Արման (տպ. Atlas)
The General Epistle (Encyclical letter) of Catholicos Nerses IV Shnorhali (1166- 1173) occupies a unique place among the monuments of Armenian canonical (ecclesiastical) law. Spiritual and political figure of the 12th century, great thinker, teacher, poet and musician, Nerses Shnorhali is a prominent representative of Armenian culture. Shnorhali is the founder of a number of new directions in medieval Armenian lyricism and prose (story in verse, historical-patriotic mournful chant, historical poem, panegyric in verse, message and wish, children's poem, pedagogical and educational poem, riddle). The literary heritage of Nerses Shnorhali (sharakans, taghs, gandzs, meghedi, liturgies, as well as chants) is one of the peaks of Armenian spiritual literature; its significance goes beyond the scope of national monody art. It is not a surprise that already during his lifetime Nerses Shnorhali was named the Sweet Singer (Ergetsokh). The prayer “I confess with faith” has a special place among the poetic works of Nerses Shnorhali, yet the pinnacle of his poetic legacy is the poem “Jesus the Son.” The works of Nerses Shnorhali are also rich in deep philosophical judgments. The pinnacle of Shnorhali’s prose is the work “Conciliar (General) Epistle,” which is the first kontakion of the newly ordained Armenian Catholicos Nerses IV Pahlavuni (1166), which was addressed to the entire Armenian nation. The “General Epistle” (“Encyclical letter”) consists of two main sections: the first is addressed to the clergy, and the second to the secular class. In it, addressing representatives of all classes and estates of Armenian society, Shnorhali pinpoints unhealthy relationships, arrogance, sins and vices manifested in public life, and warns about their harmful consequences. At the same time, deeply concerned with the restoration of society, Shnorhali, a prominent theologian, philanthropist and national figure, gives recipes and ways to get rid of these evils. Shnorhali’s exhortations are not abstract, they are not detached from life and reality, but are argued and supported by specific historical events, biblical references and everyday examples. Thus, by establishing norms of behavior and lifestyle for representatives of different estates and classes of society, Shnorhali tried to improve the health of Armenian society through prohibitions and exhortations. These also had practical significance and application. In accordance with this, the “General Epistle” is not only a valuable historical document and literary work, but also a moral work, a source of knowledge of law, which has not lost its relevance and value in our days.
Keywords: Հաղորդումներ; Ներսէս Շնորհալի; Գրական վերլուծութիւն